(untitled) (Jurnal Bahasa, 2005)
Language is frequently used as a persuasive tool among countries as a dispute resolution mechanism either through diplomatic negotiation or through arbitration or adjudication mechanisms such as the Inter-national Court of Justice in The Hague, The Netherlands. Inherent within language are a myriad of speech acts designed to con-vey either implicitly or explicitly the communicative intent of the speak-ers involved. This paper seeks to highlight speaker intention via the kinds of speech acts used in the language of Counsels representing Malaysia and Indonesia in the case concerning sovereignty over the two islands of Sipadan and Ligitan on June 3-12, 2002 at the Interna-tional Court of Justice. Data for this paper is extracted primarily from the verbatim records of Sir Elihu Lauterpacht, Q.C., C.B.E. lead Counsel for Malaysia and Sir Arthur Watts, Q.C. Counsel for the Republic of Indonesia.